THE SENSORIC QUALITY OF MEAT OF MALE LOCAL DUCKS (Anas plathyrhinchos) GIVEN BETEL (Piper betle linn) LEAVE EXTRACT SOLUTION INCLUDED IN COMMERCIAL RATION - Dihansih, Elis; Handarini, Ristika; Haerina, Nina (Jurnal Peternakan Nusantara, 2017)
The meat of local ducks generally has lower quality than chicken meat. Typical aroma, dark red color, and hard texture of duck meat affect consumers’ preference for it. This study was aimed at assessing the sensoric quality of meat of male local ducks(Anas plathyrhinchos) given betle (Piper betle Linn) leaf extract solution included in commercial ration. The study was conducted at the Poultry Farm of Department of Animal Husbandry, Faculty of Agriculture, Djuanda University, Bogor from June to August 2016. Twenty-four male local ducks aged 2 weeks with average body weight of 449.16±75.27 g were used. BR-21E commercial feed of PT Sinta Feedmill and betel leaf extract solution were used. A completely randomized design with 4 treatments and 3 replicates was used. Treatments consisted of 100% commercial feed (R0), commercial feed + 2.5% piper betel solution (R1), commercial feed + 5.0% piper betel solution (R2), and commercial feed + 7.5% piper betel solution (R3). Data were subjected to a Kruskal Wallis test. Measurements were taken on aroma, tenderness, color, taste, and juiceness. Results showed that there were significant differences (P<0.05) in color and taste. The inclusion of 2.5% piper betle extract solution in commercial rations improved the preference of panelists for the color and taste of meat of local ducks. However, treatments did not affect panelists judgement on the hedonic quality (aroma, tenderness, color, taste, and juiceness) of meat of local ducks. Key words:meat sensoric quality, male local duck, betel leaf extract solution